2011
DOI: 10.1002/jor.21564
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of knee joint gaps without bone resection: “Physiologic” extension and flexion gaps in total knee arthroplasty are asymmetric and unequal and anterior and posterior cruciate ligament resections produce different gap changes

Abstract: General agreement is that flexion and extension gaps should be equal and symmetrical in total knee arthroplasty (TKA) procedures. However, comparisons using a standard TKA approach to normal knee joints that have not undergone bone resection are currently unavailable. Since bony preparation can influence capsule and ligament tension, our purpose was to perform measurements without this influence. Ten normal cadaveric knees were assessed using a standard medial parapatellar TKA approach with patellar subluxatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 30 publications
4
44
0
Order By: Relevance
“…The flexion and extension gaps are influenced by various factors, including deformities and osteolysis [4], contractures of the soft tissue mantle [8], operative approach [9], osteophytes [10,11], and eversion of the patella [12,13]. Even preparation of the flexion gap can influence the magnitude of the extension gap [14]. Finally, bony resection can affect capsular and ligamentous tension, and thus also the size of the gaps [15].…”
Section: Introductionmentioning
confidence: 99%
“…The flexion and extension gaps are influenced by various factors, including deformities and osteolysis [4], contractures of the soft tissue mantle [8], operative approach [9], osteophytes [10,11], and eversion of the patella [12,13]. Even preparation of the flexion gap can influence the magnitude of the extension gap [14]. Finally, bony resection can affect capsular and ligamentous tension, and thus also the size of the gaps [15].…”
Section: Introductionmentioning
confidence: 99%
“…Using applied loads that just engage the soft tissue restraints, the limits of passive motion for a single degree of freedom are quantified as the extremes of the bidirectional motions of the tibia relative to the femur about a neutral position over a range of flexion angles . However prior studies were limited in that they (1) included a limited number of degrees of freedom, (2) measured the limits of passive motion over a limited range of flexion angles, (3) constrained coupled motions, and/or (4) did not address both types of patient‐to‐patient differences in the limits of passive motion …”
mentioning
confidence: 99%
“…4,[8][9][10] Using applied loads that just engage the soft tissue restraints, the limits of passive motion for a single degree of freedom are quantified as the extremes of the bidirectional motions of the tibia relative to the femur about a neutral position over a range of flexion angles. 4 However prior studies were limited in that they (1) included a limited number of degrees of freedom, 4,8,11 (2) measured the limits of passive motion over a limited range of flexion angles, 4,8,11 (3) constrained coupled motions, 9,11 and/or (4) did not address both types of patient-to-patient differences in the limits of passive motion. 4,[8][9][10][11] Accordingly, the primary objective of the present study was to determine how variable the limits of each degree of freedom are between knees by characterizing the range of the limits of passive motion of the normal tibiofemoral joint in each of four degrees of freedom over the full range of flexion without constraining coupled motions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nowakowski et al demonstrated that the ACL resection increases the extension gap, whereas the PCL resection increases the flexion gap in physiological conditions of young and healthy cadaveric specimens. 21 They removed 10 mm of the periosteum from the medial tibia. The tibial insertion of the dMCL was reported to be 6.6 AE 1.3 mm from the joint line.…”
Section: Discussionmentioning
confidence: 99%